Raising funds in the era of digital economy - SULAEMAN, Deserina (Institutional Knowledge at Singapore Management University, 2020)
The rapid advancement in technology and internet penetration have substantially increased the number of economic transactions conducted online. Platforms that connect economic agents play an important role in this digital economy. The unbridled proliferation of digital platforms calls for a closer examination of the factors that could affect the welfare of the increasing number of economic agents who participate in them. This dissertation examines the factors that could affect the welfare of agents using the setting of a crowdfunding platform where fundraisers develop campaigns to solicit funding from potential donors. These factors can be broadly categorized into three distinct groups: (1) campaign and its corresponding fundraiser characteristics, (2) other factors within the platform, and (3) other factors outside the platform. The first group of factors has been examined in a large number of studies. The second and third groups, which encompass factors external to the campaigns and fundraisers remain under-explored and therefore are the focus of this dissertation. The first essay in this dissertation explores a factor within the platform; how displaying certain campaigns more prominently on the platform affects the performance of other campaigns. Such selective prominent practice is often viewed negatively because it is perceived to place less prominent sellers at a disadvantage (Kramer & Schnurr, 2018). The findings from the first essay provide a counterpoint to this popular view by documenting a positive spill-over effect from an increase in the performance of the prominent campaigns. In particular, when the prominent campaigns perform well, market expansion occurs with more donors entering the platform, benefiting the less prominent campaigns. These findings mitigate the concern that non-neutral practices on digital platforms naturally lead to the rich getting richer and the poor getting poorer. The second essay explores a factor external to the platform; how public statements from a government official affect private donations to charitable crowdfunding campaigns. A clear pattern of ethnic homophily among fundraisers and donors, where Hispanic fundraisers receive disproportionately more donations from Hispanic donors, is observed in this setting. This pattern of homophily becomes stronger following statements from President Donald Trump. This essay documents how social media usage, particularly by a government official, can influence the dynamic within and across ethnic groups. In sum, the findings from the two essays help inform platform designers, policymakers, and government officials of the potential effects of their actions on the digital economy.